Effect of Diamondlike Carbon Coating on Reliability of Implant-Supported Crowns - Hirata, Ronaldo; Machado, Lucas Silveira [UNESP]; Bonfante, Estevam A.; Yamaguchi, Satoshi; Imazato, Satoshi; Coelho, Paulo G. (Quintessence Publishing Co Inc, 2015)
Purpose: To evaluate the effect of diamondlike carbon (DLC) coating on abutments and/or abutment screws on the reliability, characteristic strength, and Weibull modulus of implant-supported single crowns. Materials and Methods: Seventy-two external hexagon implants (Emfills Implant 4 mm diameter, 10 mm length, Emfills) were divided into four groups (n = 18 each), according to the presence or not of a DLC coating in the abutment and/or abutment screw, as follows: abutment without coating, screw without coating (AwcSwc); abutment without coating with coated screw (AwcSC); abutment coated with noncoated screw (ACSwc), and coated abutment with coated screw (ACSC). Abutments and screws were evaluated with scanning electron microscopy. The specimens were subjected to step-stress accelerated life testing in water. Use-level probability Weibull curves and reliability for a mission of 100,000 cycles at 150 N (90% two-sided confidence intervals) were calculated. Polarized light and scanning electron microscopes were used for fractographic analysis. Results: For a mission of 100,000 cycles at 150 N, reliability was 0.45 (0.20 to 0.67), 0.12 (0.00 to 0.47), 0.56 (0.17 to 0.82), and 0.44 (0.07 to 0.77) for AwcSwc, AwcSC, ACSwc, and ACSC, respectively. The probability Weibull calculation showed a Weibull modulus (m) of m = 5.50, m = 11.64, m = 16.96, and m = 15.08 and the characteristic strengths (eta, which indicates the load at which 63.2% of the specimens of each group fail) of eta = 202.67 N, eta = 206.64 N, eta = 192.54 N, and eta = 203.59 N for AwcSwc, AwcSC, ACSwc, and ACSC, respectively. Abutment screw fracture was the chief failure outcome in all groups. Conclusion: Characteristic strength values were not different among groups; neither was reliability. However, an increase in Weibull modulus (indicating low variability of the results) was observed with DLC coating of abutment or screw or both.
Keywords: abutment screw; dental implants; carbon; reliability; step-stress accelerated life testing; Weibull